Empowering Communities with Jamu Herbal Lockdown: A Community-Based Approach - Aulia, Husni Marsha; Fauzi, Muh Ali; Syamsudin, Nur; Lestari, Veronika Nugraheni Sri (Bisma : Bimbingan Swadaya Masyarakat, 2024)
The COVID-19 pandemic has created unprecedented challenges, prompting the need for alternative methods to enhance immunity. This community service project aimed to educate the residents of Tambak Rejo Village on preparing herbal remedies (Jamu Herbal Lockdown) using local spices. This service learning approach empowered the community to utilize natural resources, improving both their immunity and knowledge about herbal health. Through hands-on training, the community members learned the process of making effective herbal drinks to prevent COVID-19 transmission and promote well-being. The expected outcome is a self-sufficient community capable of continuing this practice for future health challenges.